Problem Based Learning Dalam Penguatan Kemampuan Kognitif Siswa Pada PAI di SMA 'Aisyiyah Boarding School - Wahyudin, Aini Nabilah; Salam, Mochammad Fadlani; Chadidjah, Sitti; Ibrohim, Iim; Mukhlishah, Mukhlishah (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study addresses the common issue of the dominance of the lecture method in Islamic Religious Education (PAI), which often results in passive students and limited development of critical thinking skills. Problem-Based Learning (PBL) is proposed as an innovative solution that emphasizes active, collaborative, and contextual learning. The research aims to describe the implementation of the PBL model, analyze students' cognitive abilities, and examine how PBL strengthens these cognitive abilities in PAI at SMA ‘Aisyiyah Boarding School Kabupaten Bandung. This study employed a qualitative approach with a case study method. The subjects were PAI teachers and students from grades X and XI. Data were collected through interviews, observation, and documentation. The findings indicate that the application of PBL in PAI is proven effective in boosting student engagement. Specifically, the PBL model successfully strengthened students' cognitive abilities significantly across five main aspects. It is concluded that the implementation of PBL is an appropriate strategy for enhancing both student participation and cognitive thinking skills in religious education.